Age and growth of the scalloped hammerhead shark, Sphyrna lewini (Griffith & Smith, 1834) from the Southern coast of Sinaloa, México - Anislado-Tolentino, Vicente; Gallardo Cabello, Manuel; Amezcua Linares, Felipe; Robinson Mendoza, Carlos (HIDROBIOLÓGICA, 2017)
Age and growth for the scalloped hammerhead shark (Sphyrna lewini) were determined from opaque bands (OBs) on postcephalic vertebrae from 109 organisms (44 females, 52 cm to 276 cm total length (TL) and 65 males, 47 cm to 245 cm TL) obtained bimonthly from commercial fisheries off the southern coast of Sinaloa state (23º45´25´´N and 106º05´15´´W to 21º52´N and 105º54´W) from January 2003 to February 2005. The Bowker test of symmetry and the Index of Average Percent Error, suggest that this ageing method represents an unbiased and precise age assessment. Results show that immediately after birth (in summer), the first OB was formed and in the next winter showed the second OB. Later it was observed that two OBs were formed each year, one during summer and the other during winter, influenced by the sea surface temperature (SST). Based on the comparison of five back-calculation methods, the best methods were FraserLee. The parameters of the von Bertalanffy growth function were, for females: L? = 376 cm, K = 0.1 year-1, t0 = -1.16 years, b = 3 and W? = 222 kg; for males: L? = 364 cm, K = 0.123 year-1, t0 = 1.18 years, b = 3 and W? = 193 kg. The standard index growth (?´) was 4.2 (s = 0.1). According to these results the largest sharks observed, a female of 280 cm TL would be 12.5 years old and a male of 281cm TL would be 11 years old.